CONDITIONS FOR GRAPHS ON n VERTICES WITH THE SUM OF DEGREES OF ANY TWO NONADJACENT VERTICES EQUAL TO n-2 TO BE A HAMILTONIAN GRAPH - Do, Nhu An (Trường Đại học Đà Lạt, 2024)
Let G be an undirected simple graph on \(n ≥ 3\) vertices with the degree sum of any two nonadjacent vertices in G equal to \(n - 2\). We determine the condition for G to be a Hamiltonian graph.